Performance and Viability of Lightweight Slag-Based Alkali-Activated Cement (SAAC) as an Eco-Friendly Alternative to API Oil Well Cement - Bourbour Hossein Beygi, Saeed; Rashedi, Hamid; Soltanian, Hamid; Nakhaee, Ali (Management Strategies and Engineering Sciences, 2027)
This study aimed to develop and evaluate a lightweight slag-based alkali-activated cement (SAAC) system as a sustainable alternative to conventional API Class G oil well cement and to assess its engineering performance under laboratory conditions relevant to oil and gas well cementing operations. An experimental laboratory study was conducted using ground granulated blast furnace slag activated by alkaline solutions containing sodium hydroxide, sodium silicate, and sodium metasilicate. Both two-component and powdered SAAC systems with different Blaine fineness values (2900 and 4200 cm²/g) were designed and evaluated. A series of ASTM and API-standard tests were performed, including setting time, compressive strength, flexural strength, autoclave expansion, slurry density, thickening time, free-water measurement, ultrasonic compressive strength development, and scanning electron microscopy (SEM). Optimized mixtures were further modified with microsilica and compared directly with conventional API Class G oil well cement under elevated temperature and pressure conditions. The results demonstrated that increasing slag fineness significantly reduced setting time and enhanced compressive strength. Two-component SAAC formulations generally exhibited higher compressive strength than powdered systems, although both achieved strengths comparable to or exceeding those of Portland and Class G oil well cements. Optimized SAAC mixtures showed continuous strength development over time, acceptable autoclave expansion values, and favorable flexural performance. Under API testing conditions, the selected SAAC formulations achieved thickening times within the acceptable operational range and produced no measurable free water. The microsilica-modified SAAC mixture exhibited superior early-age and long-term compressive strength compared with Class G cement. Ultrasonic strength measurements further indicated faster strength development and greater compressive resistance under high-temperature and high-pressure curing conditions. SEM observations confirmed a denser microstructure with fewer cracks in the optimized SAAC formulations, supporting the observed mechanical performance. The developed slag-based alkali-activated cement satisfied key API performance requirements and demonstrated superior environmental and engineering characteristics compared with conventional oil well cement. The optimized SAAC system showed excellent mechanical strength, adequate thickening behavior, negligible free-water production, and enhanced performance under elevated temperature and pressure conditions, indicating strong potential as a sustainable substitute for conventional oil and gas well cement.